Pemanfaatan Kartu E-Santri dalam Pengelolaan Fiskal di Pondok Pesantren Miftahul Ulum Al-Islamy: Antara Peluang dan Tantangan - Purwanto, Andi (Journal of Islamic Economics Studies and Practices, 2024)
The integration of electronic santri cards within pesantren (Islamic boarding schools) represents a significant advancement in fiscal management and operational efficiency. This study analyzes the impact of these electronic cards on both the financial management of pesantren and the daily lives of santri (students). By employing qualitative research methods, including interviews and field observations, we explore the mechanisms through which electronic santri cards facilitate financial transactions, enhance transparency, and promote a cashless environment. The findings indicate that the adoption of electronic payment systems not only streamlines financial operations but also fosters a culture of financial literacy among santri, ultimately contributing to the sustainability of pesantren